Yeast populations associated with grapes during withering and their fate during alcoholic fermentation of high‐sugar must. (19th November 2012) - Rantsiou, K.; Campolongo, S.; Alessandria, V.; Rolle, L.; Torchio, F.; Cocolin, L.
Abstract Background and Aims Grape mycobiota may be a determining factor for the population dynamics that develop during alcoholic fermentation for the production of wine. For sweet wine fermentations, high‐sugar content grape musts are employed that represent complex microbial ecosystems. The focus of this study, the Passito di Caluso, is a sweet wine produced in the North of Italy from grapes harvested in the fall and subjected to a withering process. Methods and Results The withering process was studied by sampling and microbiological analysis, while the alcoholic fermentation was followed by both culture‐dependent and culture‐independent approaches. During the withering process we observed a succession of three yeast populations associated with grapes. A high degree of species biodiversity was detected the last day of the monitoring period. The dominance of Saccharomyces cerevisiae in the inoculated fermentation was confirmed. Conclusions A succession of yeast populations was observed during grape withering; species such as Candida zemplinina, Metschnikowia fructicola and Hanseniaspora uvarum were also detected during alcoholic fermentation. Autochthonous C. zemplinina populations could play an important technological role in sweet wine production. Significance of the Study The grape mycobiota during withering was described and its fate during alcoholic fermentation determined by molecular identification methods.